Asking the Right Questions / A Guide to Critical Thinking - Browne M. Neil; Keeley Stuart M (Pearson - Prentice Hall, 2007)
This highly popular text helps students to bridge the gap between simply memorizing or blindly accepting information and the greater challenge of critical analysis and synthesis. Preface, The Benefit of Asking the Right Questions, What Are the Issue and the Conclusion, What are the Reasons, What Words or Phrases are Ambiguous, What Are the Value Conflicts and Assumptions, What are the Descriptive Assumptions, Are There Any Fallacies in the Reasoning, Are There Rival Causes, Are the Statistics Descriptive, What Significant Information is Omitted, What Reasonable Conclusions Are Possible, Practice and Review, Final Word, Index.